Assessment of Environmental Aspects of Consumer Behavior from The Perspective of Gender: A survey study - Martin ROVNAK; Anna TOMKOVA; Ivana ONDRIJOVA; Frantisek CHOVANEC (Communications of International Proceedings, 2023)
The contribution focuses on examining consumer behavior in the context of environmental attitudes. The aim of the research was to examine gender differences in the evaluation of selected attributes of environmental aspects of consumer behavior. The data were obtained through a questionnaire survey with a sample of 151 respondents. There were examined statistically significant differences in factors motivation to purchase eco-friendly products, perception of environmental protection, opinion on environmental protection, cultural orientation, perception of green advertising, and attitude towards general green advertising. Based on the results obtained through the independent samples t-test, it can concluded the statistical significance in favor of women in all environmental aspects of consumer behavior within the stated hypothesis. The research results confirm the findings of previous similar studies.
Keywords: Environmentalism; consumer behavior; gender; sustainability